1983
DOI: 10.1038/304315a0
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic lethal mutation in mice induced by retrovirus insertion into the α1(I) collagen gene

Abstract: Experimental insertion of a retrovirus into the germ line of mice has resulted in an embryonic recessive lethal mutation. Integration of the proviral genome occurred at the 5' end of the alpha 1(I) collagen gene, leading to complete transcriptional block. Developmental arrest of embryos homozygous at the mutated allele coincides with high expression of the gene in normal embryogenesis. Insertion mutagenesis by retroviruses may offer a general approach to the identification and isolation of genes which are tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
188
0
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(197 citation statements)
references
References 53 publications
6
188
0
3
Order By: Relevance
“…In fact, we previously reported that a complete lack of AA causes emphysema resulting from oxidative stress and a decrease of collagen synthesis in the lungs of SMP30/ GNL KO mice (22). Moreover, one reason why all fetuses deprived of AA died in utero could be a collagen deficiency, because col1a1 KO mice, which cannot synthesize type 1 collagen, suffer from an embryonic lethal mutation (23).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we previously reported that a complete lack of AA causes emphysema resulting from oxidative stress and a decrease of collagen synthesis in the lungs of SMP30/ GNL KO mice (22). Moreover, one reason why all fetuses deprived of AA died in utero could be a collagen deficiency, because col1a1 KO mice, which cannot synthesize type 1 collagen, suffer from an embryonic lethal mutation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Insertional mutagenesis into an already known gene, for which no mutant was yet available, was found in the mouse strain Mov 13; here, the a(1)I collagen gene (Schnieke et al, 1983) was interrupted by insertion of an exogenous retrovirus. To date, however, few of the mutated loci in transgenic animals have been characterized.…”
Section: Insertional Mutationsmentioning
confidence: 99%
“…Taking his experiments with him, he and his Hamburg colleagues continued to study genetics over the next 7 years by infecting mice with DNA viruses and retroviruses. He discovered that some inserted viruses disrupted gene activity in the early embryo, making the viruses and insertional mutagenesis a useful tool for studying development (8).…”
Section: To Germany and Backmentioning
confidence: 99%